2001
DOI: 10.1016/s0022-5347(05)66354-9
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive Implant Migration in Patients Treated for Localized Prostate Cancer With Interstitial Brachytherapy

Abstract: Radioactive implants migrated after brachytherapy for localized prostate cancer in 29% of the patients who underwent post-procedure radiography. There did not appear to be a pattern to the seed distribution. However, while the incidence was not negligible, no patient appeared to have any acute pulmonary symptoms. Therefore, while the migration of radioactive implants to the chest is a real phenomenon, it appears to have no adverse clinical consequences in the early post-procedure period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…1,2 Despite various advantages of transperineal implantation over the suprapublic approach, pulmonary embolization of implanted seeds is a concern of under-dose in the implanted target and potential damage to the lungs. [3][4][5][6][7][8][9][10][11][12][13] Steinfeld and colleagues are among the early investigators to report their findings of the pulmonary embolization of iodine-125 ͑I-125͒ seeds. 3 Nag and colleagues described seed migration of palladium-103 ͑Pd-103͒ with transperineal implantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Despite various advantages of transperineal implantation over the suprapublic approach, pulmonary embolization of implanted seeds is a concern of under-dose in the implanted target and potential damage to the lungs. [3][4][5][6][7][8][9][10][11][12][13] Steinfeld and colleagues are among the early investigators to report their findings of the pulmonary embolization of iodine-125 ͑I-125͒ seeds. 3 Nag and colleagues described seed migration of palladium-103 ͑Pd-103͒ with transperineal implantation.…”
Section: Introductionmentioning
confidence: 99%
“…However, a long term follow-up is recommended if a pulmonary seed embolization is detected. 12,13 Currently, seed migration detection is based on review of postoperative chest radiographs. Nevertheless, detection accuracy has not yet been adequately evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The strategic placement of these seeds throughout the tumor mass can provide prolonged irradiation to the tumor while limiting the radiation burden on healthy tissues. Although the success of current approaches to prostate brachytherapy is exemplified by excellent disease-free survival (24), its implementation is plagued by a number of significant limitations, including the need for general anesthesia, complicated placement procedures, seed migration to other organs, and the need for post-treatment excision for seed removal (5). We speculated that many of these limitations might be overcome by engineering a biodegradable material that a) can form injectable depots with a life span in vivo that is compatible with the half-life of the radionuclide used for treatment; and b) degrades into non-toxic products that are resorbed by the body after the radioactivity has decayed to a level that no longer poses a threat of systemic toxicity, thereby obviating the need for surgical implantation and re-excision.…”
Section: Introductionmentioning
confidence: 99%
“…Authors have reported 21%-29% of LDR patients will have loose seeds migrate to the lungs. 3,4 These seeds may be seen on chest radiographs. It is thought that seeds implanted near the exterior of the prostate migrate into the prostatic veins, which carry them from the prostate into the lungs.…”
Section: Introductionmentioning
confidence: 99%